2011
DOI: 10.3892/mmr.2011.652
|View full text |Cite
|
Sign up to set email alerts
|

Paeoniflorin modulates multidrug resistance of a human gastric cancer cell line via the inhibition of NF-κB activation

Abstract: Abstract.Research into the evasion of drug resistance and adverse effects is highly significant and urgent in the clinic. Therefore, accumulating studies have focused on the development of novel target-specific molecules related to drug resistance, and the establishment of rational therapeutic approaches. Currently, studies have shown that NF-κB activation may play an essential role in the development of chemotherapy resistance in carcinoma cells. Paeoniflorin, a principal bioactive component of the root of Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…It has been reported that the extracts like peoniflorin, curcumin and procyanidin etc. could effectively inhibit the activity of NF-κB, down-regulate the expression of ABCB1 and decrease the P-gp expression 19-23. In our works, we have employed the extract of Traditional Chinese Medicine Stemona japonica, tuberostemonine as the MDR reversal agent, to study its reversal effect on myelogenous leukemia adriamycin-resistance cells K562/ADR.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the extracts like peoniflorin, curcumin and procyanidin etc. could effectively inhibit the activity of NF-κB, down-regulate the expression of ABCB1 and decrease the P-gp expression 19-23. In our works, we have employed the extract of Traditional Chinese Medicine Stemona japonica, tuberostemonine as the MDR reversal agent, to study its reversal effect on myelogenous leukemia adriamycin-resistance cells K562/ADR.…”
Section: Discussionmentioning
confidence: 99%
“…PF, the principal component of Total glucosides of paeonia (TGP), has also been shown to exert anti-cancer and anti-proliferative activity in cultured cells as well as in animal models. Previous studies have shown that PF induces cancer cell apoptosis in gastric cancer cells, liver cancer cells, ovarian cancer cells and leukemia cells through various mechanisms, such as the modulation of the NF-kB activation pathway, Bcl-2 and Bax expression, or the MDM2-p53 pathway 32 33 34 35 36 37 38 . In these published reports, the PF concentrations were prescribed at a milligram level, which limits its use in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…In the in vivo study, we observed that oral administration of Pae significantly inhibited tumour growth and that Pae & Cis showed synergistically inhibitory effects on the growth of tumours. Some (19) concluded that Pae at non-toxic concentrations effectively modulated multidrug resistance of a human gastric cancer cell line via inhibition of nuclear factor-kappa B activation. Similarly, Hao et al (12) previously confirmed that Pae enhanced the effect of erlotinib in pancreatic cancer cells by directly suppressing human epidermal growth factor receptor-3 activation.…”
Section: Resultsmentioning
confidence: 99%